Microwave Link License Fee for 5G Backhaul Connectivity (Study Case: Indonesia) - Yusri, Alvin; Adriansyah, Nachwan Mufti; Hanuranto, Ahmad Tri (Buletin Pos dan Telekomunikasi, 2023)
Frequency is a limited resource that cannot be made by humans. Therefore, its usage needs to be regulated so new technology like 5G still get frequency allocation. The 28 GHz frequency is an option that can be used in Indonesia for 5G technology, because it gets a large bandwidth allocation, namely 112 MHz. For the frequency to be used efficiently, one of the efforts is using the frequency license fee. In Indonesia, the frequency license fee is regulated in the regulation regarding BHP ISR for microwave link services. However, prices applied in Indonesia for 5G backhaul frequencies are too low compared to other countries such as India and Australia. With the same conditions, India applies Rp. 771,207,014, Australia Rp. 142,318,583, while Indonesia applies Rp. 32,949,287 for the frequency license fee. Based on the results of calculations, simulations, and changes to the components of the BHP ISR formula, it increases the frequency license fee to Rp. 81,320,400 which experienced an increase of 146%. The new price obtained is still below the price of other countries, because other countries have a larger GDP than Indonesia. This new price expected to make frequency usage more efficient and provide an increase in state income.